FLOW OF ELLIPTICAL PARTICLE SUSPENSIONS THROUGH A CONVERGING-DIVERGING CHANNEL - Siqueira, Ivan Rosa de; Rebouças, Rodrigo Bento; Carvalho, Márcio da Silveira (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This work analyzes the flow of elliptical particle suspensions through a convergingdiverging channel. The model considers rigid elliptical particles dispersed in a Newtonian liquid, and the suspension viscosity is given by a function of the local particle concentration and particle axis aspect ratio. Shear-induced particle migration phenomena is described by the well-known Diffusive Flux Model, and the average particle orientation is given by the principal direction of a particle conformation tensor. The conformation evolution in the flow and the constitutive equation for the resulting complex liquid are adapted from classical models used to describe the behavior of suspensions of spheroids, cylinders and fibers and polymeric solutions of rod-like molecules that are almost or completely rigid. The resulting set of fully coupled, nonlinear equations is solved using a slightly variation of the DEVSS-TG/SUPG Finite Element Method. The results show the local particle concentration and average particle orientation in the flow domain, highlighting the behavior of the suspension microstructure near sheardominated and extensional-dominated regions.